STRATEGI PEMASARAN DIGITAL PADA PRODUK TEMPE, KOTA SURABAYA - Uula, Prameswari Maulidatul; Indah, Pawana Nur; abidin, Zainal (Berkala Ilmiah AGRIDEVINA, 2019)
Tempe is a traditional Indonesian food consumed by almost all levels of society. The problem experienced in marketing this product is perishable. This study aims to identify the internal and external factors of marketing tempe producers and evaluate alternative strategies for digital marketing. The method of determining the sample is purposive sampling with 40 respondents. Methods of data analysis using IE analysis, SWOT analysis, and QSPM analysis. The results show in the IE analysis, the position of the company that produces tempe is in quadrant 2 with the use of a marketing system horizontally. The SWOT analysis explains that tempe is located in quadrant 1 with the use of the power possessed to achieve marketing opportunities. QSPM analysis, the highest TAS result is an alternative strategy in the form of consumer convenience in ordering tempe through social media. DOI : https://doi.org/10.33005/adv.v8i2.1843